Functional state characteristics of central nervous system among sportsmen with different orientation of the training process - Kolomiets, O. I.; Petrushkina, N. P.; Bykov, E. V.; Yakubovskaya, I. A. (The Russian Journal of Physical Education and Sport, 2017)
The problem of physical loads influence on functional state of sportsmen`s nervous system is still urgent. From the point of view of the theory of functional systems, in adaptation provision, the main role plays central nervous system. The main characteristics of nervous system determine functional and psychological readiness of sportsmen, which is responsible for sports effectiveness, especially in situational kinds of sport (sports games and combat sports). Material. The strategy estimation of adaptation to physical load on the basis of nervous system characteristics diagnostics, which determine speed qualities of a sportsman. Research methods: scientific literature analysis and summarizing, tapping test, tiredness coefficient determination, methods of mathematical statistics. Results. The characteristics of nervous system were studied, which determine speed qualities of a sportsman and the strategy of adaptation to physical load; two groups of sportsmen (age, anthropometric indices, qualifications and the period of going in for sports almost identical) were examined. In order to estimate the main characteristics of nervous system, which condition speed qualities of a sportsman, tapping test was used. Calculated on the basis of tapping test results tiredness coefficient helped to estimate the variant of adaptation strategy to physical load. Most qualified sportsmen had a strong type of nervous system and a high level of the studied characteristics. Sportsmen from both groups had tiredness coefficient lower than 0,25 and it proves high level of resistance to tiredness and tolerant strategy of adaptation to loads. Conclusion. Examination of qualified sportsmen, who go in for acyclic kinds of sport (ice hockey and taekwondo), using tapping test helped to give a complex estimation of the functional state of sportsmen`s nervous system and determine the strategy of adaptation to maximum intensity work.